2018
DOI: 10.3847/1538-4357/aab430
|View full text |Cite
|
Sign up to set email alerts
|

Using Strong Gravitational Lensing to Identify Fossil Group Progenitors

Abstract: Fossil galaxy systems are classically thought to be the end result of galaxy group/cluster evolution, as galaxies experiencing dynamical friction sink to the center of the group potential and merge into a single, giant elliptical that dominates the rest of the members in both mass and luminosity. Most fossil systems discovered lie within z < 0.2, which leads to the question: what were these systems' progenitors? Such progenitors are expected to have imminent or ongoing major merging near the brightest group ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…A novel technique to search for FG's progenitors is the use of strong gravitational lensing in galaxy groups. Johnson et al (2018b) investigated the fraction of FGs in lensed and non-lensed galaxy groups, finding that the fraction of FGs is larger in lensed systems (13% versus 3%). They also identified 12 possible FG progenitors, that were later investigated in details in Johnson et al (2018a) using Chandra and the Hubble Space Telescope.…”
Section: Compact and Loose Groups As Progenitors Of Fossil Systemsmentioning
confidence: 99%
“…A novel technique to search for FG's progenitors is the use of strong gravitational lensing in galaxy groups. Johnson et al (2018b) investigated the fraction of FGs in lensed and non-lensed galaxy groups, finding that the fraction of FGs is larger in lensed systems (13% versus 3%). They also identified 12 possible FG progenitors, that were later investigated in details in Johnson et al (2018a) using Chandra and the Hubble Space Telescope.…”
Section: Compact and Loose Groups As Progenitors Of Fossil Systemsmentioning
confidence: 99%
“…In our previous work (Johnson et al 2018), we identified 12 Jones fossil progenitors in the CASSOWARY catalog at varying stages of BGG formation. Sloan Digital Sky Survey (SDSS) images allowed us to observe how the galaxy population of a system evolves as it makes the transition to fossil status on average, with intermediate mass galaxies being cannibalized by the BGG.…”
Section: Target Selectionmentioning
confidence: 99%
“…Finding the Cheshire Cat also demonstrated that the progenitors to today's fossil systems can be found; to that point little concerted effort had gone into locating these outside simulations (Kanagusuku et al 2016). After the Cheshire Cat's discovery, we attempted to locate more fossil progenitors in the CAmbridge Sloan Survey of Wide ARcs in the SkY (CASSOWARY) catalog of which the Cheshire Cat (CSWA 2) was a member (Johnson et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…have not yet been translated to constraints on galaxy formation scenarios. A recent study by Johnson et al (2018) estimates that a substantial percentage of lensing systems within the group mass range are fossil or pre-fossil groups. If this is indeed the case, models of such lenses could provide a new and independent diagnosticbesides the common criteria to identify fossil groups through Xray observations -to assess whether a lens in question is in fact a fossil system, in contrast to a more standard group.…”
Section: Introductionmentioning
confidence: 99%